2016
DOI: 10.1016/j.bbr.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in object-in-place but not relative recency performance in the APPswe/PS1dE9 mouse model of Alzheimer’s disease: Implications for object recognition

Abstract: Performance was examined on three variants of the spontaneous object recognition (SOR) task, in 5-month old APPswe/PS1dE9 mice and wild-type littermate controls. A deficit was observed in an object-in-place (OIP) task, in which mice are preexposed to four different objects in specific locations, and then at test two of the objects swap locations (Experiment 2). Typically more exploration is seen of the objects which have switched location, which is taken as evidence of a retrieval-generated priming mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 71 publications
2
16
1
Order By: Relevance
“…Second, both tasks were matched in the durations of both preexposure and test, and in the number of objects employed. Third, in contrast to the findings of Bonardi et al (2016), there was no sign of any APP/PS1 deficit in the relative recency task -if anything the effect was numerically larger in the APP/PS1 animals.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Second, both tasks were matched in the durations of both preexposure and test, and in the number of objects employed. Third, in contrast to the findings of Bonardi et al (2016), there was no sign of any APP/PS1 deficit in the relative recency task -if anything the effect was numerically larger in the APP/PS1 animals.…”
Section: Discussioncontrasting
confidence: 87%
“…First, we concluded that the young transgenic mice are selectively impaired on the retrieval-generated priming process, and that their intact SOR performance depends on self-generated priming. But self-generated priming is inherently transient: given enough time all the stimulus elements will become inactive again, meaning that SOR at longer delays cannot be due to this process (Bonardi et al, 2016). It follows that these transgenic animals should only show normal SOR at relatively short sample-test delays -and this is not the case: Bonardi et al (2016) demonstrated intact SOR performance with a 24-hour delay between sample and test in these animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicate that soluble, oligomeric Aβ and tau are two major factors of synaptotoxicities [10,11]. Additionally, several studies found that dendrites and dendritic spines near amyloid plaques suffer severer damage in APP/PS1 transgenic mice, revealing the spatial correlation between Aβ, plaques, and synaptic abnormalities [12,13]. Therefore, synaptic plasticity impairment could be related to AD progression.…”
Section: Introductionmentioning
confidence: 91%